1989
DOI: 10.1149/1.2096868
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Mechanisms for Zinc Exposed to the Atmosphere

Abstract: Physical and chemical information on zinc corrosion layer formation, evolution, morphology, and chemical makeup is organized and presented, together with information on minerals containing zinc and other crystalline structures that might be expected to be present. The chemical reactions involved in the formation of these constituents during the corrosion process are then surveyed. The pH of the aqueous surface film is found to be crucial to the corrosion process, since it controls the dissolution of the passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
145
0
11

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(163 citation statements)
references
References 43 publications
(82 reference statements)
7
145
0
11
Order By: Relevance
“…This finding may be attributed to formation of ZnO (zincite). When zinc is exposed out-doors initially form zinc oxides [14] that may be transformed into a basic zinc compound. It is possible that ZnO identified in this sample resulted from the corrosion of freshly exposed zinc.…”
Section: 2 2 a Al Lt Te Er Re Ed D M Ma At Te Er Ri Ia Al Ls Smentioning
confidence: 99%
“…This finding may be attributed to formation of ZnO (zincite). When zinc is exposed out-doors initially form zinc oxides [14] that may be transformed into a basic zinc compound. It is possible that ZnO identified in this sample resulted from the corrosion of freshly exposed zinc.…”
Section: 2 2 a Al Lt Te Er Re Ed D M Ma At Te Er Ri Ia Al Ls Smentioning
confidence: 99%
“…Pongamia glabra (Vent); Derris indica (Lamk.)] which belongs to family Leguminosae and sub-family Papilionaceae [2]. It is a medium sized glabrous, perennial tree grows in the littoral regions of South Eastern Asia and Australia [3].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of corrosion products formed on the steels caused by atmospheric corrosion has been investigated in various exposure conditions. [4][5][6][7] Oesch et al 8) have reported the effect of air pollutants such as SO 2 and NO 2 on the corrosion of Zn and other light metals. The effect of corrosion products formed on electrodeposited zinc alloy coatings during atmospheric corrosion has also been reported.…”
Section: Introductionmentioning
confidence: 99%